KOORDINASI, BUDAYA ORGANISASI DAN PELAKSANAAN TUGAS PEGAWAI - Novran Putra (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Coordination, Organizational Culture and Employee Duties. This study aims to investigate the influence of organizational culture on the coordination and execution of tasks of Spatial Planning and Building by employees. This research method is quantitative descriptive using statistics. The study population was all employees of the Department of Spatial Planning and Building Pekanbaru City amounting to 21 people and all the population sampled. In addition, the community is taken as many as 31 people at random method incidental. Data collection techniques are questionnaires and observation. Analysis of data using multiple linear regression. The results showed that the coordination with the organizational culture positive and significant impact on the implementation of employee duties. However restribusi coordination and organizational culture on the implementation of the duties of employees only 61.3% and the remaining 38.7% is determined by other factors.